Economic growth, financial development, and institutions : a review of the literature - Muhammad Sodbir Hamzah; Hussin Abdullah; Mohamad Shukri Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2019)
Economic growth is affected by financial development, spurring researchers to engage in studying the indicators as well as the extent of the effect of financial development. However, the effect might differ between countries because of unique institutional quality in term of corruptions level, government bureaucracy, law and order, and risk of investment. Hence, the main aim of this study is to look at the effect of financial development on economic growth and the effect of institutions in interacting with financial development. To achieve the aim, theoretical and empirical studies are reviewed focusing on the effect of institutions and financial development on economic growth. The findings revealed that in general, indicators for financial development can be associated with the banking sector, stock market or trade openness. Upon interacting with institutions, the effect becomes more significant depending on the level on the countries’ institutional quality. Further studies are necessary in looking at the effect between countries and to assess the impact by contemplating the institutional quality.